2022
DOI: 10.1155/2022/4264314
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase-1 (PON-1) Arylesterase Activity Levels in Patients with Coronary Artery Disease: A Meta-Analysis

Abstract: Aim. To review and compare the PON-1 arylesterase activity between coronary artery disease (CAD) and non-CAD patients. Methods. Data were obtained by searching MEDLINE and Scopus for all investigations published between January 1, 2000 and March 1, 2021 comparing PON-1 arylesterase activity between CAD and controls. Results. Twenty studies, based on 5417 patients, met the inclusion criteria and were included in the analysis. A random effect model revealed that PON-1 arylesterase activity was significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The results shown in Table (1) showed a high significant decrease with a probability level (P≤ 0.0006) in the activity of aryl esterase in the serums of patients with atherosclerosis (71. The results of the current study agreed with the previous results [27] [28] , which showed that aryl esterase activity was inversely related to the risk of developing cardiovascular diseases, including atherosclerosis, as the results showed a decrease in the concentration of aryl esterase in patients with atherosclerosis compared to healthy subjects, and this is due to the increase in oxidative stress processes in patients, causing an increase in lipid peroxides in the serum, which works to inhibit the enzyme, so its effectiveness decreases in patients [29] Troponin T level:…”
Section: Measuring the Level Of The Aryl Esterasesupporting
confidence: 93%
“…The results shown in Table (1) showed a high significant decrease with a probability level (P≤ 0.0006) in the activity of aryl esterase in the serums of patients with atherosclerosis (71. The results of the current study agreed with the previous results [27] [28] , which showed that aryl esterase activity was inversely related to the risk of developing cardiovascular diseases, including atherosclerosis, as the results showed a decrease in the concentration of aryl esterase in patients with atherosclerosis compared to healthy subjects, and this is due to the increase in oxidative stress processes in patients, causing an increase in lipid peroxides in the serum, which works to inhibit the enzyme, so its effectiveness decreases in patients [29] Troponin T level:…”
Section: Measuring the Level Of The Aryl Esterasesupporting
confidence: 93%
“…Paraoxonase-1 (PON-1) is an enzyme synthesized in the liver residing on high-density lipoprotein (HDL) that catalyzes the hydrolysis of various aromatic carboxylic acid esters, organophosphates, and lactones [38]. Paraoxonase-1 has many enzymatic activities, such as lactonase, thiolactonase, arylesterase, and aryldialkylphosphatase (commonly known as paraoxonase) [39]. In humans, a strong negative correlation between PON-1 activity and serum concentrations of lipid oxidation markers has been observed [40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the HDL accessory proteins also accomplish actions in health and disease, including neurological diseases [ 63 , 64 ]. Paraoxonase-1 (PON-1), an accessory protein of HDL, is an enzyme that hydrolyzes oxHDL [ 65 ]. An issue of remarkable importance is to investigate whether PON-1 is also able to hydrolyze oxHDL.…”
Section: Discussionmentioning
confidence: 99%